Hospital policy and nurses’ knowledge on healthcare-associated infection prevention: A case study from General Hospital of Aisyiyah St. Khadijah Pinrang - Syifa Fauziah; Devy Febrianti; Zulkarnain Sulaiman (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Healthcare-associated infections (HAIs) remain a critical public health concern worldwide, contributing to increased morbidity, mortality, and healthcare costs. However, studies focusing on the interplay between hospital policy and nursing staff knowledge in rural healthcare settings remain limited. This study aims to analyze the relationship between hospital policies and nurses’ knowledge in preventing HAIs at General Hospital of Aisyiyah St. Khadijah Pinrang. A quantitative approach was employed involving 36 respondents selected through total sampling. Data were gathered using observations, questionnaires, and documentation, and analyzed using the chi-square test via SPSS. The findings revealed a statistically significant relationship (p = 0.000, p < 0.05) between hospital policy and the level of nurses’ knowledge regarding HAI prevention. These results highlight the critical role of supportive institutional policies and informed nursing staff in mitigating infection risks during healthcare delivery. The study underscores the need for integrated institutional strategies and continuous professional education to enhance patient safety, particularly in rural hospital settings where resource limitations pose added challenges.